2016
DOI: 10.1139/cjes-2015-0228
|View full text |Cite
|
Sign up to set email alerts
|

Earth evolution and dynamics—a tribute to Kevin Burke

Abstract: Kevin Burke's original and thought-provoking contributions have been published steadily for the past sixty years, and more than a decade ago he set out to resolve how plate tectonics and mantle plumes interact by proposing a simple conceptual model, which we will refer to as "the Burkian Earth". On the Burkian Earth, mantle plumes take us from the deepest mantle to sub-lithospheric depths, where partial melting occurs, and to the surface, where hotspot lavas erupt today, and where large igneous provinces and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 106 publications
0
65
1
Order By: Relevance
“…As can be seen in the temperature field (see Figures c–e, right panel), plumes rise primarily at the edges of the dense piles, as inferred from hotspots, large igneous provinces, and kimberlites (Steinberger & Torsvik, ; Torsvik et al, , ), although these correlations have been questioned (Austermann et al, ; Davies et al, ). However, thermal instabilities grow along the CMB and are subsequently pushed toward the pile, where they reshape the edge of the dense material during ascent.…”
Section: Observed Pile Structuresmentioning
confidence: 97%
“…As can be seen in the temperature field (see Figures c–e, right panel), plumes rise primarily at the edges of the dense piles, as inferred from hotspots, large igneous provinces, and kimberlites (Steinberger & Torsvik, ; Torsvik et al, , ), although these correlations have been questioned (Austermann et al, ; Davies et al, ). However, thermal instabilities grow along the CMB and are subsequently pushed toward the pile, where they reshape the edge of the dense material during ascent.…”
Section: Observed Pile Structuresmentioning
confidence: 97%
“…Although subsequent work of Burke and Torsvik (), Burke et al (), and Torsvik et al (, , ) corroborated this association of major hot spots with the edges of the low‐speed zones, others have challenged this association, by arguing that such correlations do not pass statistical tests (e.g., Austermann et al, ; Davies et al, ). Responses to these criticisms by Doubrovine et al () and Torsvik et al () demonstrate that among those active in this debate, the question is not settled. Part of the conflict stems from the set of hot spots included in such tests.…”
Section: A Chemically Stratified Lower Mantle Hot Spots Plumes Andmentioning
confidence: 99%
“…At mid-Cretaceous time, the central North American kimberlite corridor lies >1500 km to the west of the western edge of the African LLSVP and cannot be related to this feature [Currie and Beaumont, 2011]. More recently, Torsvik et al [2016] concluded that mid-Cretaceous North American kimberlites are not sourced from plumes from the deep mantle, as global tomography illustrates this region is cold and of high velocity. Somerset Island kimberlites are not related to the proposed high Arctic large igneous province (HALIP) plume head (initiated at 130 Ma); it is too old in relation to the kimberlite ages (97-93 Ma) and 1200 km distal ( Figure 1).…”
Section: Geodynamic Processes and Magmatic Triggers 541 On The Absmentioning
confidence: 99%
“…These magmas give rise to a wide variety of landforms and intrusions similar to those associated with smallvolume alkali basalt volcanic systems [Kjarsgaard, 2007]. It has been variably related to subduction processes [e.g., Sharp, 1974;McCandless, 1999;Currie and Beaumont, 2011], mantle plume hot spot tracks [e.g., Crough et al, 1980;le Roex, 1986;Heaman and Kjarsgaard, 2000], mantle plumes associated with large superswell features in the mantle [e.g., Torsvik et al, 2010Torsvik et al, , 2016, and precursory activity to major flood basalt events [e.g., Heaman et al, 2003]. However, despite decades of study the origin of the transport magma, kimberlite, remains controversial.…”
Section: Introductionmentioning
confidence: 99%